A Pilot Randomized-Controlled Trial on the Effect of CPAP Treatment on Glycemic Control in Gestational Diabetes: Study Design and Methods - Pamidi, Sushmita; Meltzer, Sara J.; Garfield, Natasha; Lavigne, Lorraine; Olha, Allen; Khalyfa, Ahamed; Benedetti, Andrea; Tremblay, Geneviève; Gagnon, Robert; Rey, Evelyne; Dasgupta, Kaberi; Kimoff, R. John (Frontiers in Endocrinology, 2018)
Background: Gestational diabetes (GDM) is associated with adverse short- and long-term maternal and fetal outcomes. Observational data support a link between sleep-disordered breathing (SDB) during pregnancy and GDM. However, it is unknown whether treatment of SDB with continuous positive airway pressure (CPAP) improves glucose control in this patient population. In addition, CPAP adherence and feasibility as a treatment option in pregnancy is unknown. This pilot randomized, controlled trial aims to primarily determine the feasibility of CPAP treatment in pregnant women with SDB and GDM. This study is also investigating the effect of SDB treatment on 24-h glucose profiles as an exploratory outcome. Objectives: To describe the study methodology in this ongoing study of pregnant women with GDM and SDB. Patients and Methods: Pregnant women with GDM and SDB defined by apnea-hypopnea index (AHI) ≥10 (Chicago Scoring Criteria) on level 2 polysomnography are randomized to either auto titrating CPAP (experimental group) or a nasal dilator strip (control group) until delivery. The primary outcome, objectively-assessed adherence to CPAP, is measured over the course of the treatment period using device-specific software. Recruitment and retention rates will be calculated to assess the feasibility for planning future trials. Twenty-four hour glucose profiles are measured over a 72-h period using the continuous glucose monitoring (CGM) system, before and after the intervention. Conclusion: The results of this study will be highly informative to determine whether CPAP is a feasible treatment for pregnant women with GDM and SDB, a specialized population at risk for substantial comorbidity. The trial results will ultimately be useful in planning future SDB treatment trials in pregnancy and GDM. The study is registered on clinicaltrials.gov (NCT02245659).